Endourological Treatment of Renoureteral Lithiasis in Major Outpatient Surgery Regime - García-Cano Fernández, Alba María; Szczesniewski Dudzik, Juliusz Jan; González Montes, Laura; Boronat Catalá, Juan; Rodríguez Castro, Percy Miguel; Llanes gonzález, Luis (Revista Cubana de Urología, 2023)
Introduction: The high prevalence of urinary lithiasis, together with medical advances and the need for efficiency in the consumption of healthcare resources, are driving the performance of procedures in major outpatient surgery without compromising the quality of care. Objectives: To evaluate the efficacy of endourological procedures in the treatment of renoureteral lithiasis under major outpatient surgery in a series of cases. Methods: Descriptive, longitudinal and retrospective review of 79 patients undergoing semi-rigid ureterorenoscopy and retrograde intrarenal surgery at the Hospital Universitario de Getafe between June-2018 and March-2020 for the treatment of urolithiasis in major outpatient surgery. A descriptive and multivariate statistical analysis of patient characteristics, urolithiasis, surgery and complications was performed. Results: The 53.2 % (42/79) had a previous ureteral catheter. The stone-free rate was 81%, with a median number of procedures of 1(1 - 4). The mean stone size was significantly larger in those who were not stone free (11.6 mm) compared to those who were stone free (9.3 mm); (p = 0.04). Predictors of success were smaller stone size (OR = 0.850) and absence of previous catheter (OR = 0.25). Intraoperative complications occurred in 15.2% (12/79), and postoperative in 26.6 % (21/79), 100 % minor according to the Clavien-Dindo classification. Admission was required in 25.3 % (20/79) of patients. Only 5.1 % (4/79) were readmitted. Regarding complications, we found no significant differences in the variables analyzed or in the logistic regression model. Conclusions: Endourological treatments of lithiasis in major outpatient surgery are safe and effective procedures. Smaller lithiasis size and absence of previous catheter are predictors of freedom from postoperative debris.